THE IMPORTANCE OF CUSTOMER RELATIONSHIP MANAGEMENT (CRM) IN MARKETING - Lutfullayeva Sarvinozkhon Azizkhonovna (Web of Journals Publishing, 2023)
This article delves into the critical role of Customer Relationship Management (CRM) within the realm of marketing. With contemporary business landscapes becoming increasingly customer-centric, CRM has emerged as a pivotal strategy for fostering lasting customer relationships, enhancing brand loyalty, and driving revenue growth. This study examines the significance of CRM as a strategic tool and investigates its multifaceted impact on marketing outcomes. Through a comprehensive analysis of existing literature and case studies, this article underscores the pivotal role of CRM in modern marketing strategies. The research methodology involves a systematic review of peer-reviewed articles, industry reports, and empirical studies, providing a holistic understanding of CRM's multifaceted contributions to marketing success. By analyzing key implementation strategies and their outcomes, this study aims to offer valuable insights into the effective integration of CRM practices to achieve sustainable marketing excellence.
Keywords: Customer Relationship Management, CRM, marketing, customer-centric, brand loyalty.